Discussion of “Financial reporting opacity and informed trading by international institutional investors” - Bushee, Brian J. (Journal of Accounting and Economics, 2012)
Maffett (this issue) finds that the opacity of a firm's information environment affects the degree of informed trade by institutional investors. In this discussion, I address the key research design choices involved in studies of opacity and informed trading and I relate the results to the literature on institutional investor performance and stock selection. I suggest that future work investigate the role of discretionary opacity in facilitating informed trade as part of the cost–benefit trade-off of the opacity decision maker (e.g., managers, analysts); test the relative effects of opacity on private information, liquidity, and price correction speed; and examine how institutional investors select which opaque firms to hold.